Language and social justice - Mantero, Miguel; Watzke, John L.; Miller, Paul Chamness (Readings in language studies., 2022)
Language and Social Justice is the fourth volume of the Readings in Language Studies series published by the International Society for Language Studies, Inc. Edited by Miguel Mantero, John L. Watzke, and Paul Chamness Miller, volume four sustains the society's mission to organize and disseminate the work of its contributing members through peer-reviewed publications. The book presents international perspectives on language and social justice in three thematic sections: culture, teaching practices & pedagogy, and policy. A resource for scholars and students, Language and Social Justice represents the latest scholarship in new and emergent areas of inquiry.